2014
DOI: 10.1111/psyp.12286
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the sequential processes involved in a cued continuous performance test

Abstract: We aimed to clarify sequential processes for cue and imperative stimuli (targets/nontargets) in a continuous performance test (CPT), and how the preparatory contingent negative variation (CNV) affects physiological and behavioral responses. Single-trial event-related potentials (ERPs) obtained from 70 participants during a cued CPT were baselined to the cue (BtC) to include the CNV, or to the imperatives (BtI) to remove the CNV. Principal components analysis obtained cue and imperative ERP components, and cong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Visual N1, N2, and P3b, and auditory N2, P3a, and P3b were all larger to targets than nontargets. These findings are broadly similar with previous oddball studies [ 49 54 ]. As the purpose of this study was to evaluate the effects of SLT, these target/nontarget differences together with the components that were not sensitive to treatment with SLT (visual N1, P2, N2, P3a, and P3b, and auditory P2, N2, and P3b) will not be discussed further.…”
Section: Discussionsupporting
confidence: 93%
“…Visual N1, N2, and P3b, and auditory N2, P3a, and P3b were all larger to targets than nontargets. These findings are broadly similar with previous oddball studies [ 49 54 ]. As the purpose of this study was to evaluate the effects of SLT, these target/nontarget differences together with the components that were not sensitive to treatment with SLT (visual N1, P2, N2, P3a, and P3b, and auditory P2, N2, and P3b) will not be discussed further.…”
Section: Discussionsupporting
confidence: 93%
“…The limitations to these methods are recognized with both the temporal PCA of ERP data and the grouping of band activity according to traditionally defined frequency limits, restricting the electrophysiological information available for analysis. Temporal PCA, however, has been reliably applied in studies of sequential ERP response activity for its ability to separate overlapping components that spatial PCAs cannot (Barry & De Blasio, ; Barry, De Blasio, Fogarty, & Karamacoska, ; Karamacoska, Barry, Steiner, & De Blasio, ; Kayser & Tenke, ; Kayser et al, ). Furthermore, the utility of spatial PCA holds value when assessing specified components (markedly the P3b) within large electrode arrays, and as the present study had several components of interest, this was not pursued for component extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the regularity in the current paradigm (fixed ISI) may have led to a stronger CNV (cf. Steiner et al, 2014b ), which has been shown to influence the N1 (Karamacoska et al, 2015 ). Future research could clarify this by employing the same paradigm used here, but varying the SOA around a 1 s mean to obviate the CNV and test whether the N1 enhancement to increases in TTI observed in Steiner et al ( 2014b ) can be replicated in this paradigm.…”
Section: Discussionmentioning
confidence: 99%